Preparation of Plants, Seeds and Image Seeds Collections of Mashhad Area Weeds - Mohammad Reza Bagheri; Mohammad Hassan Rashed Mohassel; Mahmood Reza Golzarian (علوم و فناوری بذر ایران, 2019)
This research was performed to investigate, identify and naming the weeds of mashhad area, also studying and introducing the seeds of this plant with attention to their morphological characteristics. The onset of this study was started by collecting 205 weed species and mounted on herbarium sheets. In the next phase and at the time of fully maturity of seeds, seed of each species collected and after purification of seeds, pure seeds obtained and were poured in glass vials. In attention to Absence of the prefabricated equipments for protection and displaying seeds we designed and built a case for this purpose. In final stage, considering the importance of seed images in seeds identification and studying the morphological characteristics of seeds, we prepared a set of high quality images from collected seeds. Results of this study could use as a reference for seed identification of weeds in this area and as a source for studying the morphological features of these seeds.